Management of fibrosing pancreatitis in children presenting with obstructive jaundice. Issue 5 (1st November 1998) - Sylvester, F A; Shuckett, B; Cutz, E; Durie, P R; Marcon, M A
Abstract : Background —Children with fibrosing pancreatitis are conventionally treated surgically to relieve common bile duct (CBD) obstruction caused by pancreatic compression. Residual pancreatic function has not been formally tested in these patients. Aims —To evaluate the usefulness of non-surgical temporary drainage in children with fibrosing pancreatitis and to assess pancreatic function after resolution of their CBD obstruction. Patients —Four children (1.5–13 years; three girls). Methods and results —Abdominal sonography and computed tomography revealed diffuse enlargement of the pancreas, predominantly the head. The CBD was dilated due to compression by the head of the pancreas. Pancreatic biopsy specimens obtained in three patients showed notable acinar cell atrophy and extensive fibrosis. Cystic fibrosis was excluded. No other cause of pancreatitis was identified. Pancreatic tissue from one patient contained viral DNA sequences for parvovirus B19 detected by polymerase chain reaction; serum IgM to parvovirus was positive. Three patients had temporary drainage of the CBD and one patient underwent a choledochojejunostomy. Serial imaging studies revealed resolution of the CBD obstruction with reduction in pancreatic size. Exocrine pancreatic function deteriorated. Three patients developed pancreatic insufficiency within two to four months of presentation. The fourth patient has notably diminished pancreatic function, but remains pancreatic sufficient. None has diabetes mellitus. Conclusions —Temporary drainage of the CBD obstruction is recommended in fibrosing pancreatitis in children along with close monitoring of the clinical course, before considering surgery.